Proceedings of the 9th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2017
DOI: 10.1145/3122986.3123011
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multimodal Feedback Techniques for In-Car Mid-Air Gesture Interaction

Abstract: This paper presents an investigation into the effects of different feedback modalities on mid-air gesture interaction for infotainment systems in cars. Car crashes and near-crash events are most commonly caused by driver distraction. Mid-air interaction is a way of reducing driver distraction by reducing visual demand from infotainment. Despite a range of available modalities, feedback in mid-air gesture systems is generally provided through visual displays. We conducted a simulated driving study to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 34 publications
2
36
1
Order By: Relevance
“…It reduces mental workload [39,32] and provides a sense of control of the outcomes of one's actions [8]. It decreases eyes-off-the-road time [41] and improves user satisfaction [33]. For these reasons, a growing body of research is investigating feedback for mid-air interaction in driving situations.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It reduces mental workload [39,32] and provides a sense of control of the outcomes of one's actions [8]. It decreases eyes-off-the-road time [41] and improves user satisfaction [33]. For these reasons, a growing body of research is investigating feedback for mid-air interaction in driving situations.…”
Section: Related Workmentioning
confidence: 99%
“…Shakeri et al [41] have investigated different unimodal feedback types such as visual, auditory, peripheral visual, and cutaneous push haptic feedback for mid-air gesture interaction in cars. They found that non-visual feedback reduced eyesoff-the-road time significantly and did not influence driving performance negatively.…”
Section: Related Workmentioning
confidence: 99%
“…In a driving situation, traditional visual feedback is located in an eyes-off-the-road position whereas peripheral feedback can be perceived whilst looking ahead. Peripheral feedback has been shown to decrease eyes-off-the-road time compared to traditional visual feedback for mid-air gesture interaction [8]. Cutaneous push feedback on the steering wheel can be presented to the steering hand when gesturing.…”
Section: Related Workmentioning
confidence: 99%
“…In a previous study on unimodal feedback for mid-air gestures [8], we investigated the effectiveness of visual, auditory, cutaneous push, and peripheral lights feedback for mid-air gestures in cars (see Figure 1). We found that providing non-visual feedback decreased eyes-off-the-road time significantly, however mental demand was higher in the non-visual conditions.…”
Section: Related Workmentioning
confidence: 99%
“…Motion-based interaction through mid-air gestures has become increasingly popular with the advancement of motion sensors (e.g. Microsoft HoloLens, Leap Motion) and has been employed in a diverse range of applications such as interactive TV, vehicles, and public displays [9,10,13]. Research [4,11] has found that older adults (aged 60 and older) may face greater challenges when interacting through mid-air gestures due to age-related decline in motor control, limited range of motion [5] and a lack of familiarity with this novel input method [6,8,12], however this issue is far from being tackled and fully understood.…”
Section: Introductionmentioning
confidence: 99%